Prognosis of atrial fibrillation radiofrequency ablation: Iodine-123-MIBG cardiac innervation imaging. (8th February 2021) - Varlamova, Y; Zavadovsky, K; Kisteneva, I; Sazonova, S; Batalov, R
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): Russian Science Foundation BACKGROUND: To date, radiofrequency catheter ablation (RFCA) of atrial fibrillation (AF) is a valuable treatment option. So far there are no clear predictors of the effectiveness of AF ablation. Nowadays, the association of cardiac sympathetic nervous system and the development and maintenance of AF has been showed. The association between сardiac sympathetic system impairment, assessed by 123I-MIBG scintigraphy and RFCA effectiveness was shown previously. However, the is lack of data concerning to prognostic value of MIBG scintigraphy in patients with different forms of AF – persistent (PAF) and long-standing persistent (LSPAF). PURPOSE: To study the prognostic significance of 123I-MIBG scintigraphy in RFCA efficacy in patients with persistent and long-standing persistent AF. METHODS: The study enrolled 36 patients with drug-resistant AF (both persistent (n = 20) and long-standing persistent (n = 16) forms).  All patients had comorbidity as chronic coronary syndrome and hypertension. A comparison group (n = 10) was also enrolled in the study. It includes patients with chronic coronary syndrome and arterial hypertension (without arrhythmia). All patients underwent 123I-MIBG and 99mTc-MIBI scintigraphy to evaluate the cardiac sympathetic activity and myocardial perfusion, respectively. Patients with AF performed RFCA. After of 1 year follow-up patients were examined for AF recurrence. The AF recurrence was considered to be an AF of at least 30 sec duration on a 12-lead ECG or on the Holter monitoring. RESULTS: During the follow-up period, AF recurrences were reported in 7 (35%) PAF patients and in 8 (50%) LSPAF patients. According to multivariate analysis only a high pre-ablation washout rate of 123I-MIBG (WR) in PAF patients (OR: 1.668; 95% CI: 1.093–2.548) and large pre-ablation 123I-MIBG/99mTc-MIBI mismatch score in LSPAF patients (OR: 2.155; 95% CI: 1.192–3.897) were independent predictors of AF recurrence after RFCA. ROC analysis indicated that in PAF patients with higher WR ≥ 20.8% (AUC: 0.968; Sensitivity: 100 %; Specificity: 45%; p < 0.05) and LSPAF patients with larger 123I-MIBG/99mTc-MIBI mismatch score ≥ 12.5 % (AUC: 0.942; Sensitivity: 81 %; Specificity: 28 %; p < 0.05) had a higher risk of AF recurrence after RFCA. CONCLUSION: In AF patients the incidence of arrhythmia recurrence after RFCA is associated with impaired cardiac sympathetic nervous activity. In PAF patients the values of 123I-MIBG washout rate can predict AF recurrence. In LSPAF patients innervation/perfusion mismatch has prognostic value in terms of AF recurrence.